Distribution of uterine histological changes in aged captive cheetahs (Acinonyx jubatus). Issue 5 (30th July 2020) - Penfold, Miles J.; Schulman, Martin L.; Clift, Sarah; du Plessis, Lisa; Thompson, Peter N.; Hartman, Marthinus J.
Abstract: The histological effect on the felid uterus of sterilization, via ovariectomy or salpingectomy, is currently unknown. To investigate the association of ovariectomy or salpingectomy with uterine health, it is first necessary to establish if changes are distributed evenly throughout the uterus. Both laparoscopic ovariectomy and salpingectomy with concurrent sampling of the tip of the uterine horn are possible in the cheetah. Currently accepted practice for histopathological screening of the uterus utilizes four biopsy samples. It is not known whether this method accurately reflects the status of the entire uterus. In this study we histologically examined the uteri of six older cheetahs (one 7‐year‐old and five 10–10.5‐year‐old animals) via 21 tissue samples (three samples from seven different anatomical regions) per cheetah to determine overall uterine health. Although no defined lesions were detected, mild endometrial gland dilation, assumed to be of no functional consequence, was observed in multiple samples. The odds of observing this dilation was lowest in the uterine body and progressively increased in a cranial direction, being significantly higher at the tip of the uterine horns (OR = 11.5; 95% CI, 2.0‐65.1; p = 0.006). This supported the reliability of sampling the tip of the uterine horn to screen for endometrial gland dilation. Abstract : In this study we histologically examined the uteri of six older cheetahs (one 7‐year‐old and five 10–10.5‐year‐old animals) via 21 tissue samples (three samples from seven different anatomical regions) per cheetah to determine overall uterine health. Although no defined lesions were detected, mild endometrial gland dilation, assumed to be of no functional consequence, was observed in multiple samples. The odds of observing this dilation was lowest in the uterine body and progressively increased in a cranial direction, being significantly higher at the tip of the uterine horns. This supported the reliability of sampling the tip of the uterine horn to screen for endometrial gland dilation.